Project-based learning and student development skills - Mullai, Elvira (European Journal of Multidisciplinary Studies, 2017)
This study presents the results of a research work, which aims to highlight the benefits of learning through projects in the development of cognitive and psycho-social skills of students. Project-based learning is a contemporary teaching method where students work on a project about a topic or a particular problem that seeks to develop a variety of learning skills such as cognitive skills, social and collaborative skills, self-affirmative and leadership skills. To accomplish this work, students rely on prior knowledge of the subject and in-depth research on issues to be answered. The purpose of this paper is to highlight the positivity that the projected hours for the development of the special potentials the students have, aiming at the successful inclusion of students in the learning process. To substantiate the problem, we have also raised the research question: How does project work affect the students learning, leadership and social skills? To answer the research question of this study, we have raised the hypothesis that project work encourages the development of student learning, leadership and social skills. We have proved this problem through a qualitative observation method that was realized with the students of the eighth grade in the 9-year school "Abdulla Hida" in Elbasan, in the interlocutor project hours. From the results of the research we have come to the conclusion that through project-based learning is achieved the cognitive, social and self-empowering development of students.